2023
DOI: 10.3390/ma16020678
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Tests on the Corrosion Protection of Mild Steel in Hydrochloric Acid Environment by the Use of Pyrazole Derivative

Abstract: In this study, 1,5-diallyl-1H-pyrazolo [3,4-d] pyrimidin-4 (5H)-one (PPD) was evaluated as an anticorrosion agent for mild steel (MS) in 1 M HCl. The analysis was performed by weight loss (WL), potentiodynamic polarization measurement, and electrochemical impedance spectroscopy (EIS). The Tafel polarization showed that PPD is a mixed-type inhibitor and reaches 94% of the protective efficiency at 10−3 M. EIS results indicated that the resistance to charge transfer increases with increasing inhibitor concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…The surface morphology of mild steel before electrodeposition and composite coatings deposited on mild steel at 5, 10, 20, and 30 mA cm -2 of current density is shown in Figure 5. The morphology of bare mild steel seems to be smooth, as shown in Figure 5(a), and this work has been reported earlier [39,40]. The morphology varies from surface to surface, and at low current densities, the coating's morphology is compact and smooth; at high current densities, it becomes less compact and has coarser features.…”
Section: Morphology Analysis Of As-developed Coating At a Different C...supporting
confidence: 83%
“…The surface morphology of mild steel before electrodeposition and composite coatings deposited on mild steel at 5, 10, 20, and 30 mA cm -2 of current density is shown in Figure 5. The morphology of bare mild steel seems to be smooth, as shown in Figure 5(a), and this work has been reported earlier [39,40]. The morphology varies from surface to surface, and at low current densities, the coating's morphology is compact and smooth; at high current densities, it becomes less compact and has coarser features.…”
Section: Morphology Analysis Of As-developed Coating At a Different C...supporting
confidence: 83%
“…It can be remarked in Figure 10 b–e that with the Brij (Brij 35, Brij 56, and Brij 58P at 800 ppm) surfactants, the OLC 45 substrate zone presented a superior and improved morphological substrate compared to that of the uninhibited OLC 45 substrate, showing an appreciable ability of the surfactants to protect against corrosion. An adsorbed film is presented on the OLC 45 substrate to produce a diminution in contact (touch) with the OLC 45 specimen and the aggressive environment, which is liable for the corrosion inhibition [ 11 , 40 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the progress of new friendly organic substances (surfactants, plants extract, polymers) with anticorrosion properties that have ecological, biodegradable, cheap, and healthy characteristics for active materials represents a large domain of exploration in the area of anticorrosion protection [ 39 , 40 , 41 , 42 , 43 , 44 ]. Surfactants are organic inhibitor molecules which contain hydrocarbonate chains of diversified lengths and these variations of the attached alkyl chains can determine a notable impact on the hydrophobicity of a corrosion inhibitor [ 45 , 46 , 47 , 48 ]. The extent of the alkyl chains and the existence of π-bonds, including heteroatoms, execute a huge effect on the adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of SS/Ti(N,O) coatings, the slopes were quite similar, such that it may be concluded that the hydrogen evolution and metal dissolution were almost in equilibrium [61]. For the ALD-coated samples, except for SS/Ti(N,O)/HfO 2 -110c, the anodic slope became higher than the cathodic slope, indicating an inhibition action of the oxides by simply blocking the metal from interaction with the acidic and oxidising environment [62][63][64]. Considering the Tafel plots (Figure 17b-d), one can see that both the uncoated and Ti(N,O)-coated SS showed a local disruption of the passive layer, evidenced by the breakdown potential (Eb), giving rise to a sharp increase in the ion current density, indicating that local corrosion processes were activated.…”
Section: Electrochemical Evaluation-tafel Plotsmentioning
confidence: 89%